2020
DOI: 10.1126/sciadv.aba7606
|View full text |Cite
|
Sign up to set email alerts
|

Robust differentiation of human pluripotent stem cells into endothelial cells via temporal modulation of ETV2 with modified mRNA

Abstract: Human induced pluripotent stem cell (h-iPSC)–derived endothelial cells (h-iECs) have become a valuable tool in regenerative medicine. However, current differentiation protocols remain inefficient and lack reliability. Here, we describe a method for rapid, consistent, and highly efficient generation of h-iECs. The protocol entails the delivery of modified mRNA encoding the transcription factor ETV2 at the intermediate mesodermal stage of differentiation. This approach reproducibly differentiated 13 diverse h-iP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…They concluded that the robust and transient expression of ETV2 was sufficient to generate ECs independent of endogenous VEGFR2 and ETV2 expression. These ECs function adequately in comparison with ECFCs and ECs generated from a previous protocol ( 43 ).…”
Section: Differentiation and Characterization Of Vascular Ecs From Humentioning
confidence: 79%
See 1 more Smart Citation
“…They concluded that the robust and transient expression of ETV2 was sufficient to generate ECs independent of endogenous VEGFR2 and ETV2 expression. These ECs function adequately in comparison with ECFCs and ECs generated from a previous protocol ( 43 ).…”
Section: Differentiation and Characterization Of Vascular Ecs From Humentioning
confidence: 79%
“…Recently, Wang et al used chemically modified RNA (modRNA) to endogenously express ETV2 during the mesodermal stage of iPSC differentiation, resulting in highly efficient EC production ( 43 ). After inducing mesodermal progenitors by the addition of CHIR, modRNA was transfected into mesodermal cells via lipofection or electroporation to deliver ETV2.…”
Section: Differentiation and Characterization Of Vascular Ecs From Humentioning
confidence: 99%
“…Drug testing using heterogeneous cell populations may lead to an inaccurate conclusion, especially if it is based on ensemble measurements ( Altschuler and Wu, 2010 ). To tackle this issue, a variety of strategies can be employed, such as optimization of the differentiation protocol ( Wang et al, 2020 ), purification using genetically engineered reporter cell lines ( Hu et al, 2018 ), or magnetic-activated cell sorting (MACS) based on the desired surface marker ( Li et al, 2017 ).…”
Section: Moving Forward-what Is Next?mentioning
confidence: 99%
“…Genetically identical to the donors, iPSCs hold the promise to recapitulate individual predisposition to various risks ( Kitani et al, 2019 ; Lam et al, 2019 ). Furthermore, recent advances in iPSC differentiation strategies now enable the efficient generation of all the major cell lineages of the human cardiovascular system, including cardiomyocytes (CMs) ( Lian et al, 2012 ; Burridge et al, 2014 ), endothelial cells (ECs) ( Lian et al, 2014 ; Olmer et al, 2018 ; Williams and Wu, 2019 ; Wang et al, 2020 ), smooth muscle cells (SMCs) ( Cheung et al, 2012 ; Patsch et al, 2015 ), and cardiac fibroblasts (CFs) ( Zhang et al, 2019a ). These cells functionally and structurally resemble their counterpart primary cells.…”
Section: Introductionmentioning
confidence: 99%
“…A myriad of researchers also use fluorescence-activated cell sorting (FACS) or flow cytometry to enumerate and separate cell types. Many functional assessments are in use to further characterize cells and cultures, including assays for shear stress, nitric oxide production, tube formation, vascular networks, and perfusion [ 60 ].…”
Section: Modeling Using Hipscsmentioning
confidence: 99%